In vitro activity of seven antifungal agents against Fusarium oxysporum and expression of related regulatory genes. - Dafeng Xu; Kun Wang; Tingchun Li; Jingjing Wang; Shiji Wang; Fanna Kong; Jie Dai; Yuguo Liu; Banfeng Ruan; Benguo Zhou (PLoS ONE)
Fusarium oxysporum (F. oxysporum) is one of the main pathogenic fungus causing maize ear rot. In this study, the aims were to screen highly effective pesticides for F. oxysporum, reduce peasants' misunderstandings about pesticide application, improve disease control levels, and enhance economic efficiency. The toxicity of seven fungicides (carbendazim, pyraclostrobin, epoxiconazole, tricyclazole, azoxystrobin, difenoconazole, quintozene) on F. oxysporum were determined by the mycelium growth rate and the spore germination method, and single and compound fungicides with effective inhibitory effects on mycelial growth were screened. The RT-qPCR method was used to detect the expression levels of chitin synthetase V (ChsV), folate uptake block T (FUBT), superoxide dismutase (SOD), and peroxidase dismutase (POD) genes in pathogenic bacteria treated with the selected agents and combination of fungicides. The results showed that all seven fungicides had inhibitory effects on mycelial growth hyphae and spore germination of F. oxysporum. Epoxiconazole had the strongest inhibitory effect on mycelium growth and spore germination of F. oxysporum, with effective concentrations (EC50) of 0.047 and 0.088 μg/mL, respectively. The combination of pyraclostrobin and difenoconazole (P&D, combined at a mass ratio of 7:3) had the best inhibitory effect, with an EC50 of 0.094 μg/mL and an SR of 2.650. Epoxiconazole and the combination P&D could inhibit mycelial growth and spore germination by down-regulating ChsV, FUBT, and POD, causing oxidative stress in F. oxysporum, and reducing the occurrence of maize ear rot.